2017
DOI: 10.21448/ijsm.370128
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Volatile Compounds (VCs) in the Leaves Collected from ‘Gemlik’, ‘Halhalı’ and ‘Sarı Hasebi’ Olive Tree Varieties

Abstract: There is a considerably interest on some fruits and leaves extracts such as olive leaf, due to their beneficial health effects. Olive leaf has been consumed as tea for many years. However, the studies on volatile compounds (VCs) of leaves are scarce. Therefore, this study was aimed to evaluate of VCs in the leaves collected from 'Gemlik', 'Halhalı' and 'Sarı Hasebi' olive trees varieties grown in Hatay province. The VCs were analyzed by gas chromatography-mass spectrometry (GC-MS) using solid phase micro-extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…According to Dursun et al, (2017) α-cubebene is a major compound collected in December of olive leaves from Hatay province (Turkey). In this study it was identified only in February with a value of 10.54% [ 39 ]. Linalool was identified in February with a high value of 9.35%, while in December it was detected only with a value of less than one percent.…”
Section: Resultsmentioning
confidence: 99%
“…According to Dursun et al, (2017) α-cubebene is a major compound collected in December of olive leaves from Hatay province (Turkey). In this study it was identified only in February with a value of 10.54% [ 39 ]. Linalool was identified in February with a high value of 9.35%, while in December it was detected only with a value of less than one percent.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, statistical analysis revealed that germacrene D is also affected by the leaf surface of the sampled shoots both in laboratory and field trials. Two other VOCs, ( Z , E )-α-farnesene and heptadecane, are commonly emitted in small amounts by apple leaves and olive leaves (Bengtsson et al ., 2001; Dursun et al ., 2017). In the present study, they were directly related to the leaf surface of the shoots sampled in the laboratory trials, and their emission increased in infested plants.…”
Section: Discussionmentioning
confidence: 99%
“…Arbequina presented 68.9% of the total number of larvae counted, evidencing the preference of P. forficifera to host this cultivar, instead Koroneiki. This preference could be explained due to the emission of a greater amount of kairomones, volatile compounds that are associated with greater attractiveness of insects in vegetables and which are variable in amount among olive cultivars (DURSUN et al, 2017). However, this should be confirmed by future research.…”
Section: Introductionmentioning
confidence: 92%